Draft Annual Plan 2000-2001 Volume-II Government of Assam - Planning Commission (Planning Commission, 2000)
Draft Annual Plan 2000 - 2001 - Proposed Outlays Annual Plan 2000-2001 Physical Targets And Achievement Agriculture And Allied Activities. Annual Plan 2000-2001-Proposals for Programmes/Projects Annual Plan -2000-2001 - Proposed Outlays Financial Outlays/Expenditure for Voluntary Sector Wohbn Component (Wc) In the State Plan Programmes -I Annual Plan- 2000-2001- Financial Outlays Proposals for Women Component
Planning and Development Department Government of Assam